Plants using in postpartum care by traditional healers a review of literature - Farzana, M.U.Z.N.; Manuha, M.I.; Fahamiya, N. (Faculty of Indigenous Medicine, University of Colombo, 2016)
Medicinal plants have a vital role during pregnancy, birth and postpartum care in many rural areas. The WHO estimates that about 80% of the population living in developing countries relies almost exclusively on traditional medicine for their primary healthcare needs....
Keywords: Traditional medicine; postpartum women; primary health care